2021
DOI: 10.1097/mcg.0000000000001521
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Habitual Dietary Intake With Fecal Short-Chain Fatty Acids and Bowel Functions in Irritable Bowel Syndrome

Abstract: Background & Goals: Diet may contribute to symptoms of irritable bowel syndrome (IBS) and luminal production of putative IBS biomarkers including short-chain fatty acids (SCFAs). Study aims were to to assess relationships of habitual fiber or starch intake with fecal SCFAs in patients with IBS and healthy volunteers (HVs). Study: In 18 HVs and 30 patients with IBS (13 constipation-predominant [IBS-C] and 17 diarrhea-predominant [IBS-D]), habitual di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 58 publications
0
12
0
1
Order By: Relevance
“…Fiber intake was analyzed from 24 studies 11,15,16,43,44,[48][49][50]54,56,63,66,68,69,86,87,[89][90][91]94,98,[102][103][104][105] (N = 3388 participants with IBS, N = 7179 controls) to demonstrate lower intake in participants with IBS compared to controls with high heterogeneity (MD: −1.8 g; 95% CI: −3.0, −0.6; I 2 = 85%, Figure 3).…”
Section: Total Fibermentioning
confidence: 99%
See 1 more Smart Citation
“…Fiber intake was analyzed from 24 studies 11,15,16,43,44,[48][49][50]54,56,63,66,68,69,86,87,[89][90][91]94,98,[102][103][104][105] (N = 3388 participants with IBS, N = 7179 controls) to demonstrate lower intake in participants with IBS compared to controls with high heterogeneity (MD: −1.8 g; 95% CI: −3.0, −0.6; I 2 = 85%, Figure 3).…”
Section: Total Fibermentioning
confidence: 99%
“…Fat intake was analyzed from 19 studies 11,15,16,44,[48][49][50]54,56,62,63,69,87,89,90,[93][94][95][96][97][98][99][101][102][103][104] (N = 2369 participants with IBS, N = 5021 controls). There was no significant difference between participants with IBS and controls with moderate heterogeneity (MD: −2 g; 95% CI: −5.3, 1.2; I 2 = 59%).…”
Section: Total Fatmentioning
confidence: 99%
“…Se han publicado también varios estudios que relacionan a los TIIC con los productos que entran en la categoría de metabolitos microbianos como el butirato, pero esto sería tema de otra revisión debido a que, de acuerdo con la definición actual, no se consideran posbióticos 31,32 .…”
Section: Posbióticos En El Tratamiento De Los Trastornos De Interacci...unclassified
“…Despite these challenges, studies evaluating relationships between fecal SCFAs and quantitative features in IBS, rather than clinical phenotypes, have yielded more consistent findings. Prior research has shown an inverse correlation between fecal SCFA levels and colonic transit time (CTT) ( 10 12 ) and associations of SCFAs with stool form and frequency ( 13 , 14 ), suggesting that SCFAs are linked to physiologic features in IBS. However, it is unclear whether excreted SCFAs are stable physiological traits in IBS or whether measurements are determined by modifiable factors such as diet.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is unclear whether excreted SCFAs are stable physiological traits in IBS or whether measurements are determined by modifiable factors such as diet. Although some studies have failed to show clear changes in SCFAs after dietary interventions in IBS ( 15 , 16 ) and no clear association between SCFAs and habitual diet based on dietary recall ( 13 ), data on the effects of actual food intake during stool collection are lacking.…”
Section: Introductionmentioning
confidence: 99%